Prospective Physics Teachers' Conceptions on the Campfire: A Phenomenographic Study - GÜREL, ZEYNEP (AMER INST PHYSICS, 2018)
The aim of this study was to determine the thoughts and conceptualizations of prospective physics teachers on the way to follow to build and maintain a campfire and the effect of lived experience on them with a phenomenographic approach. The sample consisted of prospective physics teachers taking the course called Physics in Nature: Camping and Visiting Practices in Spring 2009. An open-ended question was prepared depending on participants' lived experiences of the campfire at a residential camp by the researchers and it was asked the whole class. Then categories were determined and thereby the association between these categories was shown through two maps, one for participants and one for nonparticipants of the camp. The categories and subcategories for the two groups were the same except for a few, but there was a difference between the hierarchies of categories and subcategories. This made an important difference in terms of practicality in favor of participants, and all these were considered to be an effect of lived experience.
Keywords: EXPERIENCES; KNOWLEDGE